Bæredygtig national transportplanlægning - Sørensen, Claus Hedegaard; Pryn, Marie Ridley; Cornet, Yannik; Salling, Kim Bang (Proceedings from the Annual Transport Conference at Aalborg University, 2014)
Sustainable Development and Decision Support are two conceptual ’procedures’ which are not yet aligned. Sustainability has been a buzzword used by politicians, planners and stakeholders for enabling a trend towards the sustainable society. It is generally expected that the three dimensions of the economy, society and the environment must be included in any measurable sustainability path. However these do not provide much guidance as to how to prioritize impacts within and between the dimensions. A conceptualized approach to sustainability based on the nested model is therefore presented seeking to provide an alternative approach to sustainable transportation assessment, namely the SUSTAIN DSS model. This model is based on a review of basic principles of sustainability presented by the Brundtland Commission report, and operationalized by the use of Multi-Criteria Decision Analysis (MCDA) and the Analytic Hierarchy Process (AHP). The planning and decision-making process related to the new connection across the Roskilde fjord in Frederikssund is used as a case study. It is found that the SUSTAIN DSS model provides a foundation for connecting better to the essence of sustainable development as well as to integrate sustainability into the practice.